Numerical analysis of steel-reinforced concrete composite girders = Analiza numeryczna stalowo-żelbetowych dźwigarów zespolonych - Szajna, Waldemar St. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents a numerical model of a typical composite girder which consists of a strip of a reinforced concrete slab resting on a steel beam. Compatibility of horizontal displacements is assumed in the slab-beam contact region. The structure is subjected to unidirectional bending. The cross-section is divided into layers, either steel or concrete, and then analysed by applying non-linear characteristics of materials. The problem is solved by employing the finite element method. For a nonlinear system of equations the modified Newton-Raphson method is used. Examples of verification and illustration are enclosed. The stages of the composite structures under increasing loads are analysed in details.
Keywords: dźwigary; konstrukcje zepolone; analiza numeryczna; metoda elementów skończonych; composite structures; numerical modelling; Finite Element Method (FEM); nonlinear analysis